Postpartum Depression: From Molecular Mechanisms to Clinical Management – A State-of-the-Art Review for the Obstetrician - Wojcieszak, Maja; Gęborys, Anna; Kania, Joanna; Maziarczyk, Alicja; Lambach, Jakub; Kutnik, Kacper; Woźnica, Weronika; Dąbrowska, Julia; Białogłowski, Michał; Mazurek, Katarzyna (Journal of Education, Health and Sport, 2026)
Background. Postpartum depression (PPD) is a common childbirth complication, affecting an estimated 17.2% of women worldwide. Unlike the short-lived “baby blues,” PPD is a unique neurobiological illness defined by an inability to adapt synaptically to reproductive hormone withdrawal. It is the most common cause of maternal suicide, and the offspring of PPD mothers also suffer long-lasting cognitive and emotional impairments. Aim. Our objective was to review the pathophysiology of PPD (with special emphasis on the GABAergic and immuno-inflammatory hypotheses), screening procedures and to outline a “stepped-care” management algorithm, including new neuroactive steroids. Material and Methods. A systematic literature search was conducted using PubMed/MEDLINE, Embase, and Cochrane databases (Jan 2010 – Dec 2024). We prioritized meta-analyses, randomized controlled trials (RCTs), and guidelines from major obstetric societies (ACOG, RCOG). Results. There is evidence for current hypothesis of rapid withdrawal of allopregnanolone as trigger of the development of symptoms that do not initiate the adequate GABA-A receptor reorganization in vulnerable women. Other mechanisms include HPA axis dysregulation and inflammation-induced tryptophan depletion. The gold standard for screening remains the Edinburgh Postnatal Depression Scale (EPDS) Sensitivity: 86%). Pharmacologic treatment has significantly progressed: Sertraline remains the first-line SSRI due to safety in lactation, but the FDA approval of Zuranolone (2023) provides a mechanism-specific, rapid-acting therapeutic option addressing the underlying hormonal dysregulation. Conclusions. Obstetricians are the primary gatekeepers for maternal mental health. Preparation of obstetricians to identify women at higher risk and to treat with pharmacotherapy is an essential part of contemporary obstetric practice.